PKM INTERNSHIP STUDENT COMPETENCY TRAINING IN THE FIELD OF PHOTOSHOP CS 6 GRAPHIC DESIGN - Ari Amir Alkodri; R Burham Isnanto; R ferry bakti atmaja; Bambang Adi Winoto; Andreani Andreani (LP2M STP Mataram, 2022)
In this era of increasingly advanced technological development, skills and competencies in the digital field are increasingly needed to remain capable to compete in the future. One way to get these skills is to take vocational education in the field of computer technology. However, many vocational education graduates are not ready to work and lack competence. This training program activity aims to further strengthen students' competencies and provide students with experience in the world of work. At the end of the program, participants gain additional knowledge, experience and understanding of computer competence as well as an overview of a professional work ethic.